Structural changes in industry: competence-based approach on the role of a project administrator - A. A. Tikhomirov (Вестник университета)
This article discusses an approach to the formation of a competence model on the example of the role of a project administrator based on the experience of introducing changes to the methodology used in projects implemented at industrial enterprises of various sectors. Special attention is paid to how, based on modern project management methodologies, it is possible to form a functional role model in the organisational structure of a project as well as to apply basic knowledge of the set theory. The article considers the division of the general functionality of the project administrator role into the most important, in the opinion of the author, relevant areas of the activity. In addition to the enlarged sets of decomposed functions, an approach to the subsequent decomposition steps is given, the results of which form the corresponding detailed subsets of the functions required to perform the previously specified project role. We present an approach to the formation of a mathematical record of the functional role as well as the relationship between the functions and competencies of an employee who is planned to be assigned to a particular project role. When detailing the functionality, using the example of the project administrator role, some of the tools applied from the practical experience of the author are given. In addition to the analysed example, this article provides a formalised universal graphical project model as well as a brief description of other key roles.